Availability, accessibility and use of information and communication technologies by undergraduates in Nigerian universities: what role for university libraries? (2007)
Information and Communication Technologies (ICTs) facilitate access to electronic information which has become invaluable in complementing traditional library resources. The objective of this study was to determine location, accessibility and use of ICTs by undergraduates. Three universities were purposively selected and undergraduates from four faculties were randomly selected. Questionnaire, interview and observation were the data collection methods used. A total of 700 respondents were used for the study while cross tabulation and percentages were the data analysis methods. ICTs were used in university libraries, computer laboratories and cybercafes on the campuses and it was found that not all the ICTs available were accessible to undergraduates in the. university’ libraries. The academic tasks for which ICTs were used were assignments, class work, projects, seminar and term papers. University libraries still need to provide more ICTs for students’ use. This could be achieved through encouraging the intervention of private initiatives as this could in turn promote more use of ICTs.